Enantioselective Organophotocatalytic Telescoped Synthesis of a Chiral Privileged Active Pharmaceutical Ingredient. Issue 33 (4th May 2022) - Herbrik, Fabian; Sanz, Miguel; Puglisi, Alessandra; Rossi, Sergio; Benaglia, Maurizio
Abstract: The continuous flow, enantioselective, organophotoredox catalytic asymmetric alkylation of aldehydes was studied, by using a homemade, custom‐designed photoreactor for reactions under cryogenic conditions. Going from microfluidic conditions up to a 10 mL mesofluidic reactor, an increase of productivity by almost 18000 % compared to the batch reaction was demonstrated. Finally, for the first time, a stereoselective photoredox organocatalytic continuous flow reaction in a fully telescoped process for an active pharmaceutical ingredient (API)synthesis was successfully achieved. The final process consists of four units of operation: visible light‐driven asymmetric catalytic benzylation under continuous flow, inline continuous work‐up, neutralisation and a final oxidative amidation step afforded the pharmaceutically active molecule in 95 % e.e. Abstract : An efficient in‐flow catalytic enantioselective organophotoredox alkylation of aldehydes has been successfully developed (up to 98 % e.e.) and applied to the fully telescoped synthesis of a chiral active pharmaceutical ingredient (API), consisting of four units of operation: in‐flow asymmetric benzylation, inline continuous work‐up, neutralisation and oxidative amidation. By using flow technologies, the productivity was increased by almost 200 times compared to the batch reaction.